2005
DOI: 10.1021/jf040392j
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Metabolism of the Conjugates of 3-Nitropropanol and 3-Nitropropionic Acid in Forages Poisonous to Livestock

Abstract: Glycosides of 3-nitro-1-propanol (nitropropanol) and glucose esters of 3-nitro-1-propanoic acid (nitropropionic acid) occur in many forages distributed throughout the world. Systemically, nitropropionic acid irreversibly inactivates succinate dehydrogenase, thereby blocking ATP formation. Nitropropanol is not toxic per se in mammals but is converted to nitropropionic acid by hepatic alcohol dehydrogenase. Nitrotoxins can be metabolized by rumen microbes, which may provide a mechanism for detoxification. At lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 88 publications
0
46
0
1
Order By: Relevance
“…Anderson et al have found that 3-nitropropionic acid is metabolized by the ruminal microbes or rapidly absorbed in the reticulo-rumen (50). When given intravenously, 3-nitropropionic acid was lethal to sheep in a concentration of 52 mg/kg body weight (50). This paper is the first to report on the ability of M. circinelloides for production of 3-nitropropionic acid in culture.…”
Section: Figure 7 Lc-esi-ms/ms Srm Chromatogram Of An Extract Of Mucmentioning
confidence: 69%
See 1 more Smart Citation
“…Anderson et al have found that 3-nitropropionic acid is metabolized by the ruminal microbes or rapidly absorbed in the reticulo-rumen (50). When given intravenously, 3-nitropropionic acid was lethal to sheep in a concentration of 52 mg/kg body weight (50). This paper is the first to report on the ability of M. circinelloides for production of 3-nitropropionic acid in culture.…”
Section: Figure 7 Lc-esi-ms/ms Srm Chromatogram Of An Extract Of Mucmentioning
confidence: 69%
“…contaminated sugarcane (53). Anderson et al have found that 3-nitropropionic acid is metabolized by the ruminal microbes or rapidly absorbed in the reticulo-rumen (50). When given intravenously, 3-nitropropionic acid was lethal to sheep in a concentration of 52 mg/kg body weight (50).…”
Section: Figure 7 Lc-esi-ms/ms Srm Chromatogram Of An Extract Of Mucmentioning
confidence: 99%
“…45; 3x enriched) 199 probably evolved as a protective measure against toxic xenobiotic alcohols, 200 and is capable of metabolizing a variety of alcoholic drugs. 201 Although alcohol oxidation by ADH generates toxic aldehydes, 202 the reaction is actually kinetically favoured in the opposite direction, 203 indicating that ADH may protect against aldehydes generated by bacteria 204 or by microsomal oxidation. 205 With its high affinity for aldehydes, phagophore-associated ADH could possibly be able to recognize aldehyde-protein adducts, ubiquitously formed, e.g., in alcoholic liver disease.…”
Section: Autophagosomal Membrane Proteinsmentioning
confidence: 99%
“…Anti-nutritive toxic compounds such as beta-N-oxalyl-L-alpha and beta-diaminopropionic acid are present in Lathyrus sativus seeds [16]. Similarly, 3-nitro-1-propionic acid and 3-nitro-1-propanol are present in the seeds and foliage of many legumes [17]. This work will lead the way for neutralization of toxins in other legumes using similar approaches.…”
Section: Discussionmentioning
confidence: 86%